2019
DOI: 10.1016/j.hpb.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Pre-, peri- and post-operative factors for the development of pancreatic fistula after pancreatic surgery

Abstract: Background: The most hazardous complication to pancreatic surgery is the development of a postoperative pancreatic fistula (POPF). Appropriate understanding of the underlying pathophysiology, risk factors and perioperative mechanisms may allow for better management and use of preventive measures.Methods: Systematic literature search using the English PubMed literature up to April 2019, with emphasis on the past 5 years. Results: Several risk scores have been developed but none are perfect in predicting POPF ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 84 publications
1
33
2
2
Order By: Relevance
“…The hard pancreatic structure due to the peritumoral fibrous tissue is thought to reduce the risk of pancreatic fistulas for patients with pancreatic ductal adenocarcinomas [22], but this was not confirmed in our study group, where there were no statistically significant differences in distribution of peritumoral fibrous tissue depending on histological diagnosis.…”
Section: Discussioncontrasting
confidence: 71%
“…The hard pancreatic structure due to the peritumoral fibrous tissue is thought to reduce the risk of pancreatic fistulas for patients with pancreatic ductal adenocarcinomas [22], but this was not confirmed in our study group, where there were no statistically significant differences in distribution of peritumoral fibrous tissue depending on histological diagnosis.…”
Section: Discussioncontrasting
confidence: 71%
“…As it is the most common complication, avoiding it is the strategy to follow. In a review, Søreide et al 23 associated fistula with acute pancreatitis, complication of underlying diseases, malnutrition and surgical site infection. This study revealed the development of GED as a consequence of malnutrition followed by fistulas and formation of intra-abdominal collections.…”
Section: Discussionmentioning
confidence: 99%
“…Attention should be paid to the pathology of POPF. It has been reported that pancreatic fistula may be related to following aspects: [22][23][24] (1) When tissue and tissue are anastomosed, the needle passes through the pancreatic tissue and may break through the expanded small pancreatic duct, which may also cause pinhole infiltration, thereby causing leakage of pancreatic juice; (2) When the pancreas and intestine are anastomosed, there must be a gap between the needles, which causes pancreatic juice to leak out from the gap; (3) There is high pressure in the jejunal intestine tube. At the end of surgery, if the intestines cannot work normally and peristalsis is weak, and there is a long jejunal bridge after co-operating with the pancreas, this can easily cause pancreatic juice and bile retention in the intestine.…”
Section: Discussionmentioning
confidence: 99%